New Conjugated Compound T5 Epidioxy-Sterol-ANB Inhibits the Growth of Mycobacterium tuberculosis Affecting the Cholesterol and Folate Pathways - Baena, Andres; Vasco, Emanuel; Pastrana, Manuel; Alzate, Juan F.; Barrera, Luis F.; Martínez, Alejandro (Frontiers in Microbiology, 2020)
The upsurge and persistence of drug resistant strains of Mycobacterium tuberculosis (Mtb) is an important limitant to the battery of drugs available for the elimination of tuberculosis (TB). To avoid the future scarce of antibiotics against Mtb is important to discover new effective anti-mycobacterial agents. In this study, we present data from a series of experiments to determine in vitro and in vivo anti-mycobacterial activity of a library of epidioxy-sterol analogs. We test 15 compounds for their ability to reduce the viability of Mtb. We found that one compound called T5 epidioxy-sterol-ANB, has significant bactericidal activity against Mtb in vitro specifically inside macrophages but without effectivity in axenic cultures. A viability assay conﬁrms that this T5 compound is less toxic for macrophages in vitro as compared to the current Mtb drug Rifampicin, at higher concentrations. We use a transcriptomic analysis of Mtb inside macrophages after T5 epidioxy-sterol-ANB treatment, and we found a significant down-regulation of enzymes involved in the cholesterol and folic acid pathways. In vivo, significant differences were found in the lungs and spleen CFUs of Mtb infected mice treated with the T5 epidioxy-sterol-ANB as compared with the untreated control group, which provides additional evidence of the effectivity of the T5 compound. Altogether these results conﬁrm the potential of this T5 epidioxy-sterol-ANB compound against Mtb.